COVID-19 in a leukemic child - Muhd Helmi, Muhd Alwi; Taib, Fahisham; Nik Yusof, Nik Khairulddin; Nasir, Ariffin; Mohamad, Norsarwany (Malaysian Paediatrics Association (MPA), 2021)
The newly emerged SARS-CoV-2 Betacoronavirus strain has infected more than one million people worldwide. The COVID-19 infection in children was reported to be less severe compared to adults. At this point, there were limited data available to describe the effect of COVID-19 infection in immunocompromised children. We reported a case of SARS-CoV-2 infection in an immunocompromised child with a delayed virus clearance. The report signifies the variability in the severity of SARS-CoV-2 infection in immunocompromised children together with a prolonged period of viral clearance.